Universal salvation in late antiquity : Porphyry of Tyre and the Pagan-Christian debate - Simmons, Michael Bland (Oxford studies in late antiquity, 2015)
This title explores the background to the effort of the Neoplatonist philosopher Porphyry (c.A.D. 232-305) to devise a system of universal salvation as a means of countering the Christian soteriological challenge, and the Christian reactions to this, notably from Eusebius of Caesarea